Solvent free oxidation of benzyl alcohol to produce benzaldehyde using bimetallic Au-Pd supported catalysts - Sarhan, Sanaa Tareq (2018)
The study of using a gold and palladium as heterogeneous catalyst is commonly investigated for many oxidation process now days especially in benzyl alcohol oxidation. In this respect, the main goal of this research is to study the influence of oxidant with Au-Pd bimetallic catalyst to achieve highest potential to obtain more benzaldehyde. The monometallic and bimetallic catalysts are synthesized via impregnation and sol-immobilization methods. The structural, texturalphysicochemical, morphological, and thermal characteristics of the synthesized catalysts hav investigated by using X-Ray Diffraction (XRD), Thermogravimetric Analysis (TGA), Transmission Electron Microscope (TEM) , High Resolution Transmission Electron Microscopy (HRTEM) , Brunauer-Emmett-Teller (BET), Field Emission Scanning Electron Microscopy (FESEM) and Temperature Programmed Desorption (TPDNH3). On the other hand, an examination of the reusability and leaching of gold and palladium into benzyl alcohol also was carried out. As a result, sol-immobilization methods was shown produced stable catalysts, highly active density of both metal loading, highest strength, large surface area and more selective for the oxidation benzyl alcohol. The result also revealed that 1wt%Au-Pd/C catalyst prepared by solimmobilizations methods showed the best catalytic activity in the oxidation of benzyl alcohol at temperature of 80 ̊C for 4hours. Comparing with mono Au or Pd catalyst, bimetallic Au-Pd gave alloy formation that contribute a synergy effects and showed an improvement for conversion and selectivity on the benzyl alcohol oxidation. In addition, the effect of variable parameters, such as reaction temperature, effect of different support , heat treatment conditions, oxidant ratio, reaction time and metal loading ratio have been evaluated for optimization to produce more benzaldehyde. It was found that the activity and selectivity of the oxidation benzyl alcohol was highly dependent on these variables. A good reusability of the catalysts with less of leaching gold into the product has obtained also. As a conclusion, the oxidation of benzyl alcohol was successfully studied and the best catalyst was Au-Pd/C that synthesized by using sol-immobilization. This catalyst was found had a good distribution of narrowed small particles (2.79nm). Furthermore, the importance of the H2O2 as an oxidant have been proven in this research.